TINJAUAN TERHADAP PEMAHAMAN JEMAAT TENTANG KARYA ROH KUDUS DALAM IBADAH ONLINE DI GEREJA BETHEL TABERNAKEL KRISTUS ALFA OMEGA SEMARANG - Gidion, Gidion; Jahja, Soendoro; Astuti, Tri; Tambunan, Debora Tiurlan; Herika, Herika; Manik, Disetra Fiser (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
Understanding the role of the Holy Spirit in online worship services certainly affects the attitude of the congregation to participate in online worship services. Researchers were interested in examining the congregation's understanding of the role of the Holy Spirit in online worship services at the Gereja Bethel Tabernakel Kristus Alfa Omega Puri Anjasmoro Semarang, because there are indications that the congregation is less enthusiastic about participating in online worship. Even though the online worship link has been provided by the church, during worship hours the congregation does not conduct online worship. Based on interviews with several congregations, information was found that the congregation felt more of God's power in worship at the church (onsite) than online worship outside the church. The approach used in this research is a quantitative descriptive method. The results show that the congregation's understanding is very high. The background factor of the respondents who had been in the congregation for a long time was the most influential on the congregation's understanding of the role of the Holy Spirit in online worship